PENGEMBANGAN DIGITALISASI POTENSI USAHA MIKRO KECIL DAN MENENGAH KRUPUK AYAM ”DWIK JAYA” - Lestari, Ni Made Abelia Ayu; Putri, Ni Made Tika; Herayani, Ni Pande Iin; Wijaya, Putu Yudi (JURNAL SEWAKA BHAKTI, 2025)
Micro, Small, and Medium Enterprises (MSME) play a crucial role in Indonesia’s economy, particularly in creating jobs and increasing community income. Kerupuk ayam “Dwik Jaya” is one example of an MSME that has the potential to grow through effective socialization and promotion. This study aims to explore the use of promotional videos as a strategic method for introducing product visibility and provide clear information about the advantages and production processes, thereby attracting consumer attention. The proposed problem-solving methods include identifying marketing issues, researching target markets, developing engaging video content, and providing digital marketing training for business owner. The results of the socialization activitiees indicate that promotional videos offer significant benefits for business actors. Thus, it is expexted that Kerupuk Ayam “Dwik Jaya” can improve its competitiveness in the market and positively contribute to the local economy.